Mucosa-associated lymphoid tissue lymphoma of the accessory parotid gland presenting as a simple cheek mass: A case report. Issue 36 (September 2019) - Hwang, Jae Ha; Kim, Dong Wan; Kim, Kwang Seog; Lee, Sam Yong
Abstract: Rationale: Mucosa-associated lymphoid tissue (MALT) lymphoma, also known as extranodal marginal zone B-cell lymphoma, usually occurs in the gastric mucosa, lung, lacrimal glands, and salivary glands. MALT lymphoma arising from the accessory parotid gland is extremely rare and can therefore be easily confused with other types of soft tissue masses. Patient concerns: A 56-year-old woman presented with a 1-month history of a mass on the left cheek. The mass was hard and nontender. She had a history of thymectomy 26 years ago due to myasthenia gravis. Diagnosis: A soft tissue tumor measuring 2.5 × 0.8 cm was identified in the left accessory parotid gland on ultrasonography and enhanced computed tomography (CT). Additionally, CT revealed enlargement of both lacrimal glands and an enhancing mass in the right retropharyngeal space. Under suspicion of a malignant soft tissue tumor, ultrasonography-guided fine needle aspiration biopsy was performed, with findings suggestive of marginal zone B-cell lymphoma of the accessory parotid gland. Interventions: The patient was transferred to the department of hematology for immunochemotherapy. Outcomes: The patient has received 6 cycles of rituximab with cyclophosphamide, vincristine, and prednisone chemotherapy. After 6-month follow-up, enhanced CT demonstrated complete remission. Now she is currently under periodic follow-up. Lessons: Physicians and surgeons should be aware that MALT lymphoma can occur in the accessory parotid gland. When this is suspected, careful history-taking, imaging workup, and biopsy are essential for accurate diagnosis and treatment.